Quality of Life of Caregivers of Pediatric Patients with Cancer at Kenyatta National Hospital, Kenya - Rhodah Auma Omondi; Lister Onsongo; Sarah Bett (Journal of Medicine, Nursing and Public health, 2026)
Background: Family caregivers of children diagnosed with cancer play a critical supportive role in the care of these patients. The quality-of-life (QoL) challenges experienced by these caregivers have been shown to adversely affect their care for these children. The QoL of caregivers of children with cancer at Kenyatta National Hospital (KNH) and the experienced caregiving burden were unclear. Consequently, we assessed the QoL of caregivers of pediatric patients with cancer at KNH in Kenya and its relationship with their caregiving burden. Methods: An analytical cross-sectional study was conducted among family caregivers of pediatric patients with cancer at KNH, selected using a stratified random sampling technique. The study tools were the Zarit Caregiver Burden Interview (ZBI) and the Caregiver Quality of Life Index-Cancer (CQOLC). The data were analyzed descriptively and presented as percentages, frequencies, mean, and standard deviation, while the association between the caregivers’ QoL and their caregiving burden level was evaluated using both bivariable and multivariable logistic regression analysis at a 95% confidence interval. Data analysis was performed using SPSS version 25.0. Appropriate ethical principles were observed. Results: A total of 123 caregivers of children with cancer participated in the study. The majority (90.2%, n = 111) of the caregivers had a poor quality of life. Regarding their caregiving burden level, 50 (40.7%) experienced moderate-to-severe burden, while 69 (56.1%) experienced severe burden. Higher caregiving burden was associated with higher odds of poor QoL among caregivers (aOR = 7.902; 95% CI: 2.659-36.075; p = 0.002). Conclusion: Caregivers of pediatric patients with cancer at KNH experienced considerable caregiving burden and a poor QoL, and the two positively correlated. Recommendations: The study calls on the hospital management to support caregivers of children with cancer in the hospital psychologically, emotionally, socially, and materially for them to have a better QoL and to help ease the associated caregiving burden they bear.